Factores resilientes en adolescentes que han perdido a la madre a causa de enfermedades Oncológicas (2021)
This research aims to identify resilience factors in adolescents who have lost their mothers to oncological diseases, to learn about the experiences of adolescents who have lost their mothers to oncological diseases with respect to the disease process and to analyze the personal skills that adolescents have used to cope with the death of their mother, also to recognize diversity, to understand reality. Cancer is a process of uncontrolled cellular development and can appear in almost any part of the body. The tumor can occupy the surrounding tissue and the process of metastasis can begin at different points in the body. Research conducted through the historical hermeneutic approach is based on interpretation, seen as an art, in which the underlying contents of the narratives, contexts, habits and ways of relating of those who are part of an investigation are deciphered. Research conducted through the historical hermeneutic approach is based on interpretation, seen as an art, in which the underlying contents of the narratives, contexts, habits and ways of relating of those who are part of an investigation are deciphered.